2022
DOI: 10.1002/ca.23835
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical myofascial continuum between the neck and eyes

Abstract: The posterior myofascial chain (PMC) or superficial back line encompasses a series of muscles interlinked by the deep fascia, extending from the foot to the fascial sheath of the eyeball. The deep cervical fascia of the neck, the epicranial aponeurosis of the head, and the fascial sheath of eyeball, form the proximal PMC. Although the literature has reported an anatomical myofascial continuum between the neck, head, and eyes, the anatomical descriptions vary substantially. Moreover, there is still no plausible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…When pressure or traction is applied, those may create a range of different responses that facilitate movement [29]. Because the plantar fascia is the most distal and caudal part of the posterior muscular chain [32], proper pressure on the plantar surface stimulates the mechanoreceptors of the fascia, allowing transitory facilitation of the whole chain [31], due to the viscoelastic properties of the fascial connective tissue.…”
Section: Musculoskeletal and Fascial Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…When pressure or traction is applied, those may create a range of different responses that facilitate movement [29]. Because the plantar fascia is the most distal and caudal part of the posterior muscular chain [32], proper pressure on the plantar surface stimulates the mechanoreceptors of the fascia, allowing transitory facilitation of the whole chain [31], due to the viscoelastic properties of the fascial connective tissue.…”
Section: Musculoskeletal and Fascial Aspectsmentioning
confidence: 99%
“…In addition, the literature gives great attention to the effects of SMR, especially on the posterior muscular chain [29][30][31]. The posterior muscular chain encompasses a series of muscles interlinked by the deep fascia, extending from the foot to the fascial sheath of the eyeball [32]. For this reason, the myofascial chains are usually related to the whole-body posture [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…While one study demonstrated existence of an anatomical continuity between all muscles of the flexor region of the upper limb (85), there is evidence in support of direct serial tissue continuity from the neck and shoulder area to the forearm (86). Reportedly, an anatomical myofascial continuum exists between the neck, head, and eyes (87). Most human skeletal muscles are directly linked by fascia and connective tissue (13).…”
Section: Acupuncture As Tensegrity-based Needling (Tbn)mentioning
confidence: 99%
“…According to the fascia theory, the proximal posterior fascia chain is made up of the deep fascia of the neck and the fascia sheath of the eye. Therefore, when the fascia is damaged, it can cause discomfort in the corresponding areas [ 35 , 36 ]. Additionally, neck pain and other issues may result from irritation of joints, ligaments, fascia, and other tissues.…”
Section: Overview and Application Of The Novel Physical Therapy Techn...mentioning
confidence: 99%